SISTEM PENJADWALAN PERKULIAHAN STIE WIJAYA MULYA SURAKARTA - Renaldi, Kharisma Fajar; Utami, Yustina Retno Wahyu; Charolina, Astri (Gaung Informatika, 2014)
Lecture Scheduling System STIE Wijaya Mulya Surakarta currently using a  manual system in which all of the input data and the scheduling process is done manually so it is less efficient because it requires a relatively long time. Scheduling of lectures conducted by the head of each department of study programs in Accounting andManagement. Print schedule of lectures conducted by using Ms. Word. Manually scheduling process allows for human  error,  which  can  lead  to  conflicting  schedules  classes  in  the  absence  of  validation  when  scheduling process.  The purpose of this study was to  develop a system of scheduling lectures there on STIE Wijaya Mulya Surakarta. The system developed is scheduling classes that were previously done manually, converted into the form of an application program to be run by the Administration section. This cha nge is necessary in order to simplify, speed up and minimize errors in the process of scheduling lectures are often encountered in scheduling system manually.  System development using a structured method. The system is built to match the needs STIE Wijaya Mulya Surakarta. The system is built by using Visual Basic 6.0 and MySQL as the database. The system is equipped with validation in the process of scheduling so as to minimize errors when inputting data or when the scheduling process. This system has been  tested using blackbox methods and software quality measurement in this study using the method of McCall with the value 78.817%.   From the test results, this system is expected to facilitate and expedite the scheduling of lectures that can be applied to STIE  Wijaya Mulya Surakarta.